Monitoring and analyzing land use changes for sustainable development in Teluk Bahang, Penang, Malaysia: a GIS-based approach - Muhammad Ryza Mohd Raffay; Milad Bagheri; Azizan Marzuki; Iraj Gholami; Muhammad Anas Khairul Anuar (Journal of Engineering and Applied Science)
Abstract This study examines the vital role of environmental services in supporting human life and development in Teluk Bahang, Penang, Malaysia. Utilizing the Penang State Structure Plan 2020 (RSNPP2020) and the Draft Penang State Structure Plan 2030 (DRSNPP2030), it tracks land use patterns and changes over eight years, aiming for social, economic, and environmental sustainability. Data from the Malaysian Development Planning Department (MBPP) and the Penang Geographical Information System Center (PeGIS), along with external sources, inform the analysis. Employing Geospatial Information System (GIS) techniques, the study analyzes land use data from 2010, 2014, and 2018 using overlay and matrix methods. The results reveal a significant 18% increase in agricultural land use between 2014 and 2018 and notable shifts from agricultural to residential and commercial land uses. These changes highlight the dynamic transformation of land utilization in the region. The study recommends integrating environmental concerns into land use planning, emphasizing sustainable development strategies that balance economic growth with environmental conservation. These findings provide practical insights for policymakers to optimize land use while preserving the ecological integrity of Teluk Bahang.